The phylogeographic history, taxonomy and conservation of two cave-dwelling bat species : Miniopterus schreibersii and myotis capaccinii (Chiroptera: vespertilionidae) - Gürün, Kanat. (Thesis (Ph.D.) - Bogazici University. Institute of Environmental Sciences, 2018., 2018)
Miniopterus schreibersii and Myotis capaccinii are two cave-dwelling bat species with subcosmopolitan distributions, which are well-suited for phylogeographic studies at large geographic scales. In this study, the social and genetic structure of Miniopterus schreibersii was investigated using nuclear microsatellite and mitochondrial DNA markers, and the taxonomy and phylogeography of Myotis capaccinii was examined using mitochondrial DNA data, using samples from the entire circum-Mediterranean range of these species. Local genetic structuring previously detected among populations of Miniopterus schreibersii using mitochondrial markers was not observed for microsatellite markers, indicating male-biased dispersal. Some support was found for the fifth paradigm of postglacial expansions in Europe, which states that Anatolia might have been a primary refugium during the last glacial maxima. Regarding Myotis capaccinii, all analyses revealed the existence of three haplogroups, B, C1 and C2. The divergence of haplogroup B from C haplogroups was dated to 350,000 years BP and divergence of C1 and C2 to 130,000 years BP, indicating isolation and differentiation during multiple glacial periods. Individuals from haplogroups B and C1 were found sympatrically in the same cave, suggesting they might represent distinct species. Similarly, the C1 – C2 divergence might indicate subspecific differentiation. However, analyses of nuclear markers and phenotypic characters are required to make further subspecific and specific recommendations. Species distribution models predicted a northward movement of potentially suitable areas for Myotis capaccinii in the near future due to climate change, thus the implementation of proper environmental measures is of utmost importance for the conservation of this species complex.
Keywords: Bats -- Turkey -- Geographical distribution.; Miniopterus -- Turkey.